Performance Audit of National Rural Health Mission in Kerala (2012-2017) - CAG of India (CAG of India)
The Performance Audit was conducted to assess whether the interventions of the National Health Mission in the areas of maternal health, child health, family planning and immunisation during 2012-17 were effective in improving the health standards of women and children in the State. The Performance Audit attempted to assess whether the physical and human resources were adequate, the procurement of drugs and equipment were efficient and economical and whether the overall financial management was efficient and effective. The Performance Audit revealed deficiencies in providing delivery services to women, setting up facilities for newborn at delivery points, shortfall in infrastructure, etc., as detailed below. Government of Kerala did not release proportionate share of assistance of INR 323.22 crore during 2012-17. (Paragraph 2.7) Over 12 per cent of 24.95 lakh pregnant women who registered for Ante-Natal Care did not receive Iron and Folic Acid tablets. There was also shortfall in the percentage of women who received Tetanus Toxoid shots. (Paragraph 2.8.1) Thirty seven per cent of 24.95 lakh pregnant women were not tested for HIV. (Paragraph 2.8.2) Delivery facility was available only in 15 out of test-checked 65 institutions in selected districts, viz. Wayanad, Malappuram, Thrissur and Alappuzha. (Paragraph 2.8.4) There were deficiencies in providing free diet and other facilities to pregnant women under Janani Shishu Suraksha Karyakram. (Paragraph 2.8.8.1) Facilities like Newborn Care Corner and Newborn Stabilisation Units were not set up at all delivery points. (Paragraph 2.9.1) The objectives of District Early Intervention Centres for early detection, free treatment and management of children with health conditions were not attained as almost 83 per cent of 9,588 children identified in Alappuzha, Malappuram, Wayanad and Thrissur districts during 2016-17 did not report for further treatment. (Paragraph 2.9.3.1)